ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PENGGUNA JASA KARGO DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI - Meo, Arnoldus Ale; Gunawan, Gunawan; Priyahapsara, Istyawan (Institut Teknologi Dirgantara Adisutjipto, 2023)
This study aims to determine the effect of service quality on the satisfaction and loyalty of cargo service users at I Gusti Ngurah Rai International Airport. This study uses a quantitative descriptive method. The number of samples in this study was 125 respondents. The respondents in this study were users of cargo services at I Gusti Ngurah Rai International Airport. Determination of the sample using accidental sampling technique is a technique of determining the sample by taking respondents who happen to be available or available somewhere according to the research context. Data collection techniques by giving questionnaires to respondents, observation, and documentation. Meanwhile, to analyze the data, the Normality, Heterodicity, Linearity, Simple Regression, and t-tests were carried out using the SPSS 22.00 program. The research results show that: 1) The quality of cargo services is in the high category of 75.2%, the moderately high category is 24.8%, the moderately low category is 0% and the low category is 0%. Satisfaction of cargo service users is in the high category of 96.0%, quite high category of 4.0%, moderately low category of 0%, and low category of 0%. The loyalty of cargo service users is in the high category of 76.0%, quite a high category of 23.2%, moderately low category of 0.8%, and low category of 0%. 2) There is an effect of the quality of cargo services on the satisfaction of cargo service users as shown by the results of the t-test where the probability value (sig.) is 0.00 so that the value is less than the standard error value which is 0.05. 3) There is an effect of the quality of cargo services on the loyalty of cargo service users as shown by the results of the t-test where the probability value (sig.) is 0.016 so the value is less than the standard error value which is 0.05.